The Influence of Financial Report Content (Information) on Expected Stock Returns through the Existence of External Auditors - Orlin Cicilia (International Journal Labs, 2025)
Contents (Information) presented in financial statements are still doubtful as to whether investors use them when making decisions and consider them as a basis for analyzing investment returns. This study aims to analyze the impact of contents (information) of financial statements on expected stock returns through the existence of external auditors. Using path analysis on a sample of 104 observations from companies listed on the Indonesia Stock Exchange (IDX) in 2017–2018 across five key industrial sectors, the study finds that only working capital has a significant direct effect on expected stock returns. The presence of an external auditor did not significantly mediate the relationship between any of the financial variables and expected returns. These findings imply that investors prioritize working capital information over other financial metrics and that external assurance alone may not enhance the perceived value of financial statements. Companies should, therefore, improve the clarity and consistency of financial disclosures to strengthen investor confidence.